Removal of Ni2+ from aqueous solution by adsorption onto maize tree-trunk polyaniline composite - Tien, Pham Viet; Thanh Thuy, Mai Thi; Van Anh, Nguyen Thi; Xuan, Mai Thi; Tot, Pham Thi; The, Le Cao; Binh, Phan Thi (Vietnam Journal of Chemistry, 2016)
Maize tree-trunk polyaniline composite was prepared by chemical polymerization method. Function groups belonging to materials were characterized by IR analysis and their morphological structure was examined by SEM image. The adsorption of Ni2+ was carried out onto composite in aqueous solution via varying pH, contact time and its initial concentration. The experimental adsorption data fitted into Freundlich adsorption isotherm model (r2 = 0.9898) better than into Langmuir one (r2 = 0.6764). The adsorption followed pseudo-second order kinetic model very well (r2 = 0.9976). The maximum adsorption capacity of that composite was 66.67 mg/g which calculated from the pseudo-Langmuir equation. Keywords. Maize tree-trunk polyaniline composite, removal of Ni2+, isotherm and kinetic adsorptions.